2014
DOI: 10.1090/s1061-0022-2014-01329-5
|View full text |Cite
|
Sign up to set email alerts
|

Sharp estimates involving $A_\infty $ and $L\log L$ constants, and their applications to PDE

Abstract: It is a well-known fact that the union p>1 RH p of the Reverse Hölder classes coincides with the union p>1 A p = A ∞ of the Muckenhoupt classes, but the A ∞ constant of the weight w, which is a limit of its A p constants, is not a natural characterization for the weight in Reverse Hölder classes. In the paper, the RH 1 condition is introduced as a limiting case of the RH p inequalities as p tends to 1, and a sharp bound is found on the RH 1 constant of the weight w in terms of its A ∞ constant. Also, the sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Estimates of integral functionals as provided by the Bellman function (1.2) lead to various sharp forms of the reverse Hölder inequality, see [34]. These cases were treated in the papers [1,4,24,33,34].…”
Section: Particular Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of integral functionals as provided by the Bellman function (1.2) lead to various sharp forms of the reverse Hölder inequality, see [34]. These cases were treated in the papers [1,4,24,33,34].…”
Section: Particular Casesmentioning
confidence: 99%
“…For convenience, we assume that I = [0, 1]. We note that the function t → ϕ 1 −1 [0,1] t 0 ϕ 1 (ζ) dζ is an increasing absolutely continuous function mapping [0, 1] to [0, 1]. Let ψ be its inverse function.…”
Section: X1mentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been said in the abstract, the particular cases of this problem were treated in the papers [1,2,4,5,6,9,10,11,12,14,15,16,18,19,20,21,22,23,24] (see Section 2 for a detailed explanation). The main reason for Problem 1.1 to be solvable (and it has been heavily used in all the preceeding work) is that the function B enjoys good properties.…”
Section: Settingmentioning
confidence: 99%
“…The constant [w] A∞ was defined by Fujii [7] and Wilson [23,24], who also showed that both constants define the class A ∞ . Hytönen and Pérez [10] proved the quantitative upper bound (2) [w] A∞ [w] A exp ∞ and provided examples to show that [w] A exp ∞ can be exponentially larger than [w] A∞ (see also Beznosova and Reznikov [2]). While inequality (2) holds, it is not clear what the relationship is between A exp ∞ (w, Q) and A ∞ (w, Q) for a fixed cube Q. Hereafter we will refer to constants that contain a quantity depending on A exp ∞ (w, Q) as exponential A ∞ constants and constants depending on A ∞ (w, Q) as simply A ∞ constants.…”
Section: Introductionmentioning
confidence: 99%